Assessment of changes in autophagic vesicles in human immune cell lines exposed to nano particles - Christopher A. W. David; M. Estela del Castillo Busto; Susana Cuello-Nuñez; Heidi Goenaga-Infante; Michael Barrow; David G. Fernig; Patricia Murray; Matthew J. Rosseinsky; Andrew Owen; Neill J. Liptrott (Cell & Bioscience, 2021)
Abstract Background Safe and rational development of nanomaterials for clinical translation requires the assessment of potential biocompatibility. Autophagy, a critical homeostatic pathway intrinsically linked to cellular health and inflammation, has been shown to be affected by nanomaterials. It is, therefore, important to be able to assess possible interactions of nanomaterials with autophagic processes. Results CEM (T cell), Raji (B lymphocyte), and THP-1 (human monocyte) cell lines were subject to treatment with rapamycin and chloroquine, known to affect the autophagic process, in order to evaluate cell line-specific responses. Flow cytometric quantification of a fluorescent autophagic vacuole stain showed that maximum observable effects (105%, 446%, and 149% of negative controls) were achieved at different exposure durations (8, 6, and 24 h for CEM, Raji, and THP-1, respectively). THP-1 was subsequently utilised as a model to assess the autophagic impact of a small library of nanomaterials. Association was observed between hydrodynamic size and autophagic impact (r2 = 0.11, p = 0.004). An ELISA for p62 confirmed the greatest impact by 10 nm silver nanoparticles, abolishing p62, with 50 nm silica and 180 nm polystyrene also lowering p62 to a significant degree (50%, 74%, and 55%, respectively, p < 0.05). Conclusions This data further supports the potential for a variety of nanomaterials to interfere with autophagic processes which, in turn, may result in altered cellular function and viability. The association of particle size with impact on autophagy now warrants further investigation. Graphic abstract